KEDUDUKAN HUKUM ANAK DARI HASIL PERNIKAHAN SIRRI DAN IMPLIKASINYA TERHADAP HAK KEPERDATAAN - Yusriadi, Yusriadi; Mutiani, Santi (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to determine the legal position of children from the results of sirri marriage and its implications for civil rights. This researchers uses descriptive methods with data collection techniques through observation, interviews and documentation. The results of the study indicate that the practice of nikah sirri is very widespread in society so that it is caused by several factors such as economic factors, the desire of children to marry underage, avoid adultery and the lack of public understanding of the practice of sirri marriage itself. The position of children from sirri marriage is treated very well like children in general, namely getting a living, there is no difference in the provision of rights and obligations from parents, as well as the love of both parents. The civil rights of children from sirri marriage according to Islamic law, are in accordance with the provisions of Islamic law, because children of sirri marriage are treated like other children, while according to positive law the civil rights of children of sirri marriage are not obtained as fully as other children in general, because the sirri marriage conducted by both parents is not recorded in the official document of the country.